The SAGE handbook of evolutionary psychology - Shackelford, Todd K. (Todd Kennedy), 1971- (London : SAGE Publications Ltd, 2021)
Evolutionary psychology is an important and rapidly expanding area in the life, social, and behavioral sciences, and this Handbook represents the most comprehensive and up-to-date reference text in the field today. Chapters in this Handbook address theory and research that integrates evolutionary psychology with other life, social, and behavioral sciences, as well as with the humanities. The SAGE Handbook of Evolutionary Psychology is an essential resource for researchers, graduate students, and advanced undergraduate students in all areas of psychology, and in related disciplines across the life, social, and behavioral sciences. Part 1: Integration within Psychology; Part 2: Integration with other Life, Social, and Behavioral Sciences; and Part 3: Integration with the Humanities.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Evolutionary psychology; Human evolution